(untitled) (The International Journal for Scientific Research, 2026)
This study aimed to investigate the role of intellectual capital in achieving institutional excellence at King Abdulaziz University from the perspective of faculty members. Specifically, it sought to identify the degree of availability of the dimensions of intellectual capital, namely human capital, structural capital, and relational capital; determine the level of institutional excellence through its leadership, human, and service dimensions; examine the nature of the relationship between intellectual capital and institutional excellence; and identify statistically significant differences in the responses of the study sample according to demographic variables (gender, academic rank, and years of experience).To achieve the objectives of the study, the descriptive-correlational approach was employed. A questionnaire was used as the primary instrument for data collection. The questionnaire consisted of 33 items distributed across two main domains: intellectual capital and institutional excellence. The study was conducted on a sample of 348 faculty members at King Abdulaziz University. A range of statistical techniques was utilized, including means, standard deviations, Pearson’s correlation coefficient, the independent samples t-test, and one-way analysis of variance (ANOVA), to answer the study questions. The findings revealed that the degree of availability of the dimensions of intellectual capital (human, structural, and relational capital) at King Abdulaziz University was high, with an overall mean score of (3.59). Human capital ranked first with a mean of (3.70), followed by relational capital (3.68), while structural capital recorded a moderate level with a mean of (3.38). The overall level of institutional excellence (leadership, human, and service excellence) was moderate, with a mean score of (3.26). Leadership excellence ranked first with a high level (3.50), followed by human excellence with a moderate level (3.31), while service excellence ranked last with a moderate level (2.99).The results also indicated a statistically significant relationship at the level of (α ≤ 0.05) between the availability of intellectual capital dimensions and the level of institutional excellence. Furthermore, no statistically significant differences were found at the same significance level with respect to the demographic variables (gender, years of experience, and academic rank), either in the availability of intellectual capital or in the level of institutional excellence. Based on these findings, the researcher recommends continuing the development of university policies and professional development programs, enhancing both financial and moral incentives, strengthening participatory leadership and the flexibility of administrative and financial processes, aligning individual performance with strategic objectives, expanding academic and social motivation systems, leveraging the university’s institutional reputation through effective partnerships, and making greater use of student evaluation and feedback reports to improve educational performance. These measures are intended to transform individual capabilities into sustainable institutional performance that supports comprehensive excellence.